Caribbean realities and endogenous sustainability - Mohammed, Debbie A.; Karagiannis, Nikolaos, 1964- (Kingston, Jamaica : University of the West Indies Press, 2018)
"The contributors to Caribbean Realities and Endogenous Sustainability discuss alternative theoretical perspectives, sustainable growth-inducing economic policies, and special challenges in this era of neoliberal globalization. These perspectives, policies and challenges have to be seriously considered if appropriate interventions towards changing the Caribbean status quo and eliminating social and political ills are to be pursued. The authors evaluate past efforts and policies, criticize failed perspectives, and offer alternative strategies, policies and realistic options to the region's current socio-economic impassed and misery from a distinctly Caribbean viewpoint. The chapters are informed by such important factors as historical legacy, the role of institutions (including market and government), geopolitics and international relations, security, local culture and social psychology, which clearly stand in contrast to the starry-eyed analysis of the current orthodoxy. Overall, the essays not only expand the body of knowledge but, more importantly, provide a rich menu for alternative strategies and policies related to Caribbean international relations and social and governance ills in the twenty-first cnetury."
Introduction / Debbie A. Mohammed and Nikolaos Karagiannis; Part 1. Theoretical Issues and Alternative Perspectives. The Caribbean in the age of globalization: from plantations to resorts / Emilio Pantojas-Garc ia -- Corporate governance in the Caribbean: failures, impact and the way forward / Ron R. Sookram -- Identity formation in the English-speaking Caribbean: towards a sociodynamic perspective / Ronald Marshall and Russell Foote -- Caribbean foreign policies in the twenty-first century: from activism to improvisation in diplomacy / Jacqueline A. Braveboy-Wagner; Part 2. Economic Policies for Sustainable Growth. The post-Independence performance of Caribbean economies: the centrality of economic policy choices / Dave Seerattan -- Central American common market and Caribbean community trade policy and competitiveness on the European Union Market / Anthony Peter Gonzales -- Inclusive growth and CARICOM economies: considerations in developing a green growth framework / Debbie A. Mohammed -- Marshalling transnational partners for Caribbean development: the role of the diaspora / Indianna D. Minto-Coy; Part 3. Globalization and Special Challenges. New dimensions of regionalism in the Caribbean: an analysis of the Shanique Myrie Case / Wendy C. Grenade -- Governance and security in the Caribbean Region: what does it take? / Georgina Chami -- Advancing Caribbean competitiveness: the potential of business analytics / Gour C. Saha and Kamla Mungal -- Global forces and the role of Caribbean Trade Unios as political actors / Kristina Hinds-Harrison and Annita Montoute.
Includes bibliographical references.
NLJCols20082021
Keywords: Economic policy; Caribbean Area -- Economic policy -- 21st century; Caribbean Area -- Foreign relations -- 21st century; Sustainable development -- Caribbean Area; Corporate governance -- Caribbean Area; 15.85 history of America; Corporate governance; Sustainable development; Diplomatic relations; Economic policy; Caribbean Area; Caribbean region; 2000-2099